Indonesia's approach to reintegration: a compassionate path to security - Noor Huda Ismail (2024)
Indonesia is navigating the complex process of repatriation and reintegration of former Islamic State of Iraq and Syria affiliates, especially women and children, using a strategy that combines security measures, community support, and strategic communication. The government seeks to build public understanding and empathy toward reintegration efforts using nuanced narratives to counteract stigma and public concern. With leadership from the newly elected President Prabowo Subianto, this approach could establish Indonesia as a leader in balancing humanitarian values with counterterrorism objectives.